EFEKTIVITAS UPAYA PENERAPAN METODE TANYA JAWAB DENGAN VARIASI MEDIA PEMBELAJARAN TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MP PKN KELAS VII E MTsN JOMBANG - HARI ESTUNING (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The objectives of this class action research activity are: (1) to find out the application of the Question and Answer Method with a variety of learning media in Civics learning; and (2) to determine the effectiveness of the application of the Question and Answer Method with a variety of learning media in Civics learning towards improving student learning outcomes. The results of implementing classroom action research that took place in 3 research cycles can be concluded: 1). During PTK, efforts to apply the Question and Answer method with a variety of learning media have been well managed. 2). Learning activities using the Question and Answer method with well-managed media variations are quite effective in increasing student learning outcomes, 3). Learning media for making essays and drawing varied with the Question and Answer Method turned out to be quite effective for conveying material on Understanding Applicable Norms in Community, National and State Life, 4). The action hypothesis which states